The pattern of late gadolinium enhancement by cardiac MRI in fulminant myocarditis and its prognostic implication: a two-year follow-up study - Jiang, Luying; Zuo, Houjuan; Liu, Jingbo; Wang, Jianyu; Zhang, Kaiyue; Zhang, Chunran; Peng, Xiangyang; Liu, Yujian; Wang, Daowen; Li, Haojie; Wang, Hong (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background Myocardial fibrosis, as quantified by late gadolinium enhancement (LGE) in cardiac magnetic resonance (CMR), provides valuable prognostic information for patients with myocarditis. However, these are limited data by small sample sizes, and low event rates in fulminant myocarditis (FM). Methods and results 44 viral-FM adults applying the Chinese protocol were included in this retrospective study and divided into the low LGE group and the high LGE group according to the LGE of left ventricular (LV) mass%. CMR exams and LGE were performed after hemodynamic assistance at discharge in all FM patients. Traditional echocardiography parameters and global longitudinal strain (GLS) at discharge and two years were obtained and compared. Compared with high LGE group, both left ventricular ejection fraction (LVEF) and GLS were no significant difference in low LGE group at discharge, whereas significant difference at two-year follow-up between two groups. Moreover, the improvement of LVEF and GLS was significant in low LGE group, but not significant in high LGE group during two years. Further, LGE mass% was negatively correlated with GLS and LVEF at two-year follow-up. Conclusions: There were two distinct forms of LGE presentation in FM patients. Moreover, the cardiac function of low LGE group was significantly better than high LGE group at follow-up. LGE mass% at discharge showed significant associations with LVEF and GLS at two-year follow-up